2019
DOI: 10.3390/healthcare7040133
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Patients Affected by Depression to Share in Online Depression Communities? A Social Capital Perspective

Abstract: Online depression communities give people additional opportunities to share their experiences and exchange social support to care for themselves in fighting against depression. We aimed to explore what drives patients to share in online depression communities. We used three dimensions of social capital (structural, relational, and cognitive) to explain their sharing behaviors. We further proposed that five factors (social interaction ties, a sense of shared identity, trust, expertise, and a sense of shared val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…In the meantime, they receive less attention because of the lack of accumulation of social capital, making it difficult for them to get more emotional support. This argument is supported by a recent study by Lu et al [ 43 ], which found that it is difficult for newcomers involved in online depression communities to increase their social capital in a very short period of time and they will take a considerable amount of time contributing to the online community to establish mutual trust with other members.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the meantime, they receive less attention because of the lack of accumulation of social capital, making it difficult for them to get more emotional support. This argument is supported by a recent study by Lu et al [ 43 ], which found that it is difficult for newcomers involved in online depression communities to increase their social capital in a very short period of time and they will take a considerable amount of time contributing to the online community to establish mutual trust with other members.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, we believe that the experienced “old-timers” are more willing to share knowledge with newcomers and provide them with more support for a number of reasons [ 40 - 42 ]. First, some of them hope to develop new social ties with newcomers to enhance their social capital [ 43 ]. Second, community members with a high degree of shared identity and strong levels of trust consider it a duty to assist newcomers in improving depression treatment and outcomes and they hope that the newcomers soon became fully integrated into the online community [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…They feel morally obliged to help others within the organization on the basis of shared membership ( 23 ). In online depression communities, users view themselves as members of the community and consider it a duty to assist other users in improving depression treatment and outcomes ( 24 ). When they think they have the ability to help others, they will feel very happy.…”
Section: Theoretical Background and Research Hypothesementioning
confidence: 99%
“…An MDC for comparative analysis had to be selected. We referred to some literature and surveyed some communities, including the depression community on Baidu Tieba (Baidu, Beijing, China) [ 15 ], DingXiangYuan [ 16 ], Sunshine [ 43 ], and Zhihu. Among them, the DingXiangYuan and Sunshine are online community platforms operated by medical and psychological service institutions and only for patients who have been diagnosed with depression.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the motivation and influencing factors of members’ participation in these communities were also explored. [ 15 , 16 ]. On the other hand, some studies examined the differences between member subgroups within communities.…”
Section: Introductionmentioning
confidence: 99%